The Influence of Effective Job Analysis Methods for Determining Recruitment and Selection Criteria for Employees - Ririn Ariyanti S; Dian Ayu Dwi Permata Agustine; Kholidya Farra Safitri; Lintang Praja Musti; Mochammad Isa Anshori (Institute of Educational, Research, and Community Service, 2024)
Work is a component in an organization. Jobs should be designed to facilitate the achievement of organizational goals. The duties and responsibilities of each job determine the knowledge, skills, and abilities of those involved in the job to achieve goals, as reflected in the tasks performed. Therefore, job analysis is very important to determine the human resource needs of a company. Job analysis is needed so that managers know whether the performance of their human resources is in accordance with work procedures or not, and to know the elements that inhibit and encourage the progress of a job. Information is needed in order to understand the job and its requirements through job analysis. Apart from that, job analysis also has several specific objectives and also steps in carrying out job analysis. Job analysis has various types, namely traditional job analysis and also results-oriented job analysis and job classification. This journal is descriptive analysis. This method solves problems by describing and analyzing them, then finding solutions to the problem based on the results of the literature review. A variety of methods are used to collect information for job analysis, including interviews, questionnaires, observations, diaries, and a combination of methods. Interviews involve direct conversations with employees or potential candidates, observation means observing an individual performing their job duties, questionnaires require individuals to provide data about their work in their own words, and diaries involve employees describing their daily work activities in a log. . Combining methods is often more accurate in job analysis, because different techniques can provide a comprehensive picture of the job.